2010
DOI: 10.1089/acm.2009.0442
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Complementary Therapy on Health in a National U.S. Sample of Older Adults

Abstract: Objectives: The study objectives were to identify types of complementary therapy that are most predictive of health outcomes, including functional status, physical health-related quality of life (HRQoL), and mental HRQoL among older adults. Design: This was a prospective study. Settings/location: The study comprised computer-assisted interviews conducted in participants' homes. Results: The use of biologically based therapies predicted better functional status, such that users reported less functional impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 32 publications
0
24
2
Order By: Relevance
“…Studies on patients with serious illness such as advanced chronic kidney disease [30] and cancer [31] have shown a positive association between spirituality and health-related quality of life. However, the results from a large prospective study among older adults representative of the general population found that prayer was not predictive of health-related quality of life [32]. In this study, a worse disease-specific quality of life was significantly associated with Factor 2, which included Buddhist chanting or bible reading and prayer or meditation in the factor.…”
Section: Discussioncontrasting
confidence: 52%
“…Studies on patients with serious illness such as advanced chronic kidney disease [30] and cancer [31] have shown a positive association between spirituality and health-related quality of life. However, the results from a large prospective study among older adults representative of the general population found that prayer was not predictive of health-related quality of life [32]. In this study, a worse disease-specific quality of life was significantly associated with Factor 2, which included Buddhist chanting or bible reading and prayer or meditation in the factor.…”
Section: Discussioncontrasting
confidence: 52%
“…MBSR is practiced in most major cities and in over 250 clinics, hospitals, and HMOs in the USA and abroad (Gross et al, 2009). Mindfulness meditation programs have proliferated (Kabat-Zinn et al, 1992;Barnes et al, 2008;Nahin et al, 2009) and have seen an explosion of interest and acceptability in older adults (Nguyen et al, 2010;Loera et al, 2007;Meeks et al, 2007;Zhang et al, 2007;Ryder et al, 2008). Thus, there appears to be considerable promise to use MBSR for anxious and depressed older adults who also suffer from cognitive dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…26 This increased age may account for a portion of the usage of complementary therapies given that older adults often include these modalities in the self-management of health. 27 Survey data indicate that 27 to 88% of older adults use CAM, with higher rates reported when prayer is included, 2830 as the majority of older adults include prayer as a regular health behavior. 27,31 The increased age of those using CAM therapies in the present study may account for some of the more commonly used herbal supplements such as glucosamine, chondroitin, and ginkgo biloba, given that these products are popularly consumed to treat joint problems or to enhance memory, respectively.…”
Section: Discussionmentioning
confidence: 99%